Ukraine : Technical Assistance Report-Reforming Management and Oversight of State Assets. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses various public finance management reforms required for state-owned enterprises (SOEs), which is high priority of the government. High levels of direct and indirect state support are adding to the significant risks emanating from the SOE sector, a problem that is being exacerbated by the severe economic situation. There is a need to establish proper corporate governance arrangements through improving performance management frameworks and making SEOs accountable for poor performance, and reinforcing financial and fiscal discipline. Establishing independent Boards of Directors to perform stewardship and oversight function for public sector entities and improving transparency and reporting to the parliament and general public should form the cornerstone of the reform strategy for all SEOs.